Acceleration sensor of medium-high frequency dual FBG based on L-shaped support sensitization structure. (July 2022) - Qiu, Zhongchao; Sun, Rui; Hong, Li; Chen, Yiliu; Yu, Ruihong; Gao, Qiang
It is a key part for micro seismic crack detection, mechanical equipment operation state and structural health monitoring to measure high frequency vibration. A kind of FBG acceleration sensor based on flexure hinge is proposed targeting at the problem of existing medium-high-frequency FBG acceleration sensor's low sensitivity. Two FBGs are fixed on L-shaped support in a differential arrangement to improve sensitivity of sensor and eliminate adverse effects caused by temperature changes. Matlab and ANSYS software are used to simulate, analyze and optimize sensor. According to the simulation results, the real sensor is made, and the sensor calibration experiment is carried out. Research results show that resonant frequency of sensor is about 1700 Hz and has good linearity in flat range of 50–1000 Hz. Sensitivity of sensor can reach 18.9 pm/g, while linearity is higher than 99%, and temperature sensitivity is merely 0.074 pm/°C. Research results provide reference for researching and developing the same type of sensor, and further improving optical fiber acceleration sensor sensitivity.